Anti-corruption efforts, public perception of corruption, and government credibility in the field of real estate: An empirical analysis based on twelve provinces in China. (July 2019) - Zhang, Hongxia; Song, Yan; Tan, Shukui; Xia, Shiping; Zhang, Haitao; Jiang, Chunhong; Xiong, Ding; Cheng, Gupeng; Zhang, Lu; Lv, Yan
Abstract: Anti-corruption campaigns in China have spread rapidly throughout the field of real estate. This study measures the influence of anti-corruption efforts on public perceptions of corruption and government credibility. Based on data from twelve Chinese provinces, anti-corruption efforts, public perception of corruption, and government credibility in the field of real estate are used as variables in an empirical framework, and then analyzed with a detailed discussion of the influence of anti-corruption measures wield on the perception of corruption and political trust. The results indicate that public perception of corruption affects attitudes towards government credibility, anti-corruption efforts mitigate damage in public trust towards the central government but do not significantly mitigate damage in the trust towards provincial governments, and anti-corruption efforts fail to repair political trust effectively. Based on the results, three policy implications emerge: (1) anti-corruption efforts should be further improved as an important method for maintaining the health of the ruling party and as a method for winning public support, (2) the government should increase diversified efforts at curbing corruption, innovate anti-corruption mechanisms, and expand public participation in anti-corruption efforts, and (3) anti-corruption efforts should be strengthened by making anti-corruption an important goal of new real estate regulation. Highlights: Using data from twelve Chinese provinces, this study examines the relationships between anti-corruption efforts, public perception of corruption, and government credibility in real estate. The findings show that public perception of corruption could undermines public trust in governments and negatively affects government's credibility. Real estate anti-corruption efforts should be strengthened by making anti-corruption an important goal of new real estate regulation.